Moringa oleifera leaf alleviates functional constipation via regulating the gut microbiota and the enteric nervous system in mice - Gao, Xiaoyu; Yang, Weiqian; Li, Sijin; Liu, Shuangfeng; Yang, Weixing; Song, Shuang; Sheng, Jun; Zhao, Yan; Tian, Yang (Frontiers in Microbiology, 2023)
Moringa oleifera Lam. leaf is not only a new food resource in China, but also a traditional medicinal plant. It is commonly used in the folk to alleviate constipation, but its laxative mechanism is not fully understood. Hence we investigated it in loperamide-induced functional constipation (FC) mice. The results showed that MOAE significantly regulated not only gastrointestinal hormones and neurotransmitters in serum but also important gastrointestinal motility factors in the enteric nervous system (ENS)-interstitial cells of Cajal (ICCs)-smooth muscle cell (SMC) network. Meanwhile, MOAE attenuated intestinal inflammation, increased caecal short-chain fatty acid levels and colonic antimicrobial peptide expression, and improved the impaired intestinal barrier function in loperamide-induced FC mice. In addition, MOAE also increased faecal water content by inhibiting the mRNA expression of colonic aquaporins (Aqp3 and Aqp4) in FC mice. Interestingly and importantly, MOAE affected the intestinal microbiota by inhibiting some key "constipation-causing" microbiota, such as Bacteroidaceae, Clostridiaceae, Bacteroides, and Ruminococcus, and promoting the growth of other important "constipation-curing" microbiota, such as Butyricoccus, Tyzzerella, and Desulfovibrio. These important taxa are significantly associated with a variety of indicators of constipation. These findings suggest that MOAE can promote defecation through its rich chemical composition to modulate the ENS-ICCs-SMCs network and the gut microecosystem. MOAE can relieve the loperamide-induced FC by modulating ENS-ICCs-SMCs network. MOAE can restore the gut microbiota imbanlance induced by loperamide. Gut microbiota regulated by MOAE was correlated with constipation phenotype.